Queering Marriage : Challenging Family Formation in the United States - Kimport, Katrina, 1978- (Book collections on Project MUSE., 2014)
In-depth interviews with participants in non-traditional families are used to argue that same-sex marriage cannot be understood as simply entrenching or contesting heterosexual privilege. Instead, the author contends that these new legally-sanctioned relationships can both reinforce as well as disrupt the association of marriage and heterosexuality. She provides a nuanced, accessible, and theoretically grounded framework for understanding the powerful effect of heterosexual expectations on both sexual and social categories.